PTTA: protocolo para distribuição de conteúdo em redes tolerantes ao atraso e desconexões - Albini, Fábio Luiz Pessoa (2013)
The present work consists in the proposal of a new transport protocol for delay tolerant networks and disconnections (DTN - Delay Tolerant Network) called DTTP - Delay Tolerant Transport Protocol (in portuguese – PTTA - Protocolo de Transporte Tolerante a Atrasos). This protocol aims to provide a statistical reliability in DTNs' information delivery. For this, we use fountain codes as error correction technique. The results show the advantages of using DTTP. This work also proposes an adaptive control mechanism for the DTTP source to limit the amount of generated data. The proposed scheme aims at increasing the diversity of encoded information without increasing the load on the network. To achieve this goal the messages generation interval and TTL (Time To Live) will be handled based on some network metrics. In order to validate the efficiency of the proposed mechanism, different scenarios will be tested using the main routing protocols for DTNs. The performance results were obtained taking into account the buffer size, messages TTL and the amount of redundant information generated on the network. The simulation results, obtained through The ONE simulator, show that in the evaluated scenarios PTTA achieves an increase in the information delivery rate in a shorter time compared to other transport protocol for confirmation, thus allowing a gain in the network performance.